The effectiveness and safety of Iranian herbal medicines for treatment of premenstrual syndrome: A systematic review - Nahid Maleki-Saghooni; Fatemeh Zahra Karimi; Zahra Behboodi Moghadam; Khadigeh Mirzaii Najmabadi (Mashhad University of Medical Sciences, 2018)
Objective: Premenstrual syndrome (PMS) is one of the most common problems among women of reproductive age. The popularity of complementary/alternative therapies has grown in recent years, and these treatments have been more commonly used by women (48.9%) than men (37.8%). The aim of this systematic review was to assess effectiveness and safety of Iranian herbal medicines for treatment of premenstrual syndrome. Methods: PubMed, Scopus, Cochrane, and Google Scholar were searched along with SID, Magiran and Irandoc up to Dec 2017. Inclusion criteria consist of Iranian, published, randomized controlled trials (RCTs) using Iranian herbal medicine for treatment of reproductive age women with PMS. Eventually Eighteen RCTs met the inclusion criteria. Results: Overall, studies have shown that Vitex agnuscastus, Hypericum perforatum, Matricaria chamomilla, saffron, Curcumin, Melissa officinalis, Zataria multiflora,Wheat Germ Extract, Echinophora platyloba, Foeniculum vulgare, Valerian root extract, Citrus sinensis, Zingiber officinale andFlax seed might alleviate symptoms of PMS. Conclusion: This research demonstrated efficacy and safety of Iranian herbal medicines in alleviating PMS. Therefore, herbal medicine can be regarded as an alternative treatment for women suffering from PMS.